Plato’s Parmenides and The Knowable Many: Cosmos as Discursive Order in Hypothesis 3 - Darren Gardner (Études Platoniciennes, 2019)
In this paper, I argue that hypothesis 3 of Plato’s Parmenides presents a kind of cosmological lesson that shows why the “one” needs to be understood as an essential principle of order when examining what the “others” to the “one” would be like. At face value, the “others” are defined as opposite to the “one,” and so they cannot be “one.” Nevertheless, Parmenides claims that the “others” must not be entirely devoid of the “one.” This is because the kind of “one” in question, a form-like principle rather than a unit, is responsible for the “others” to be a discursive “many” which is required for them to be considered as “others” in the first place. I argue against the view that pairing of hypothesis 3 and 4 is merely aporetic, and propose that the lessons of hypothesis 3 can be sustained in light of hypothesis 4. The benefit of this reading is that Parmenides’ claim that denying forms would destroy the power of dialogue at 135c2 can be seen as upheld. And it contributes to the task of learning to think through the relationship of forms and participants by examining the way that discursive “others” are different from, but essentially dependent upon on a form-like principle of order.